A sequential logic model between sales performance and salesperson satisfaction in B2B markets. Issue 1 (6th May 2021) - Rodríguez, Rocío; Høgevold, Nils; Otero-Neira, Carmen; Svensson, Göran
Abstract : Purpose: The purpose of this paper is to test the relationship between objective and subjective sales performance and salespeople's economic and non-economic satisfaction in a sequential logic model. Design/methodology/approach: Based on a questionnaire survey using a deductive approach. A total of 315 companies were ultimately selected for participation in the study, to represent a range of companies from different industries and company sizes in the product-oriented business sector of Norway. A total of 236 questionnaires were returned, generating a response rate of 74.9%. Findings: The sequential logic of objective and subjective sales performance, in connection with salespeople's economic and non-economic satisfaction, reveals an underlying structure that can link existing theory and previous studies on sales performance and salesperson satisfaction in business-to-business (B2B) settings. Research limitations/implications: The results reported applying only to a B2B setting, to test whether the sequential logic model and mediating effects still hold in such setting. This study is also limited to product-oriented companies in Norway, which offers the opportunity for a future study to verify whether the refined research model also applies to service-oriented companies. Practical implications: The results indicate that the constructs of objective and subjective sales performance and salespeoplés economic and non-economic satisfaction are intertwined in a B2B setting. Specifically, these constructs are related to one another sequentially. Originality/value: Contributes to structuring in a B2B setting, the relationships between objective and subjective sales performance on the one hand and salespeoplés economic and non-economic satisfaction on the other. It also highlights two mediating effects, namely, subjective sales performance mediates the relationship effect between objective sales performance and salespeoplés economic satisfaction and salespeople economic's satisfaction mediates the relationship effect between subjective sales performance and salespeople's non-economic satisfaction.